The orientation of disaster donations: Differences in the global response to five major earthquakes - Wei, J.; Marinova, Dora (2015)
This study analyses the influence of gift giving, geographical location, political regime, and trade openness on disaster donation decisions, using five severe earthquakes that occurred between 2008 and 2012 as case studies. The results show that global disaster donation is not dominated by only philanthropy or trade interests, and that the determinants of donation decisions vary with the scale of the natural disaster and the characteristics of the disaster-affected countries. While gift giving exists in the case of middle-size earthquakes, political regimes play a very important part in the overall donation process. Countries with higher perceived corruption may donate more frequently, but those that are more democratic may be more generous in their donations. Generosity based on geographical proximity to the calamity is significant in the decision-making process for most natural disasters, yet it may have a negative effect on donations in Latin America and the Caribbean.